Influence of the playing surface on changes of direction and plantar pressures during an agility test in youth futsal players (European Journal of Sport Science, 2020)
The ability to effect a change of direction (COD) when performing high-speed actions is essential in team sports like futsal. Nevertheless, the interaction effect of sports surfaces on this ability remains unknown. This research aimed to analyse the plantar pressures and time performance of 15 youth futsal players when performing CODs on two playing surfaces with different mechanical properties. The shock absorption and vertical deformation of one synthetic flooring surface and one wooden flooring surface were assessed. CODs were evaluated using a modified version of the Agility T-Test, while total time of the test, time of CODs, and plantar pressure in CODs were all recorded. The wooden flooring surface displayed higher values of shock absorption (35.70% ± 2.87%) and vertical deformation (2.77 ± 0.38 mm) compared with the synthetic flooring (p < 0.01). Faster CODs were performed on the wooden flooring than on the synthetic flooring (-0.05 s, 95% confidence interval [CI]: -0.10 to -0.007, effect size [ES]: 0.07, p < 0.05), but no differences in total test time were found (p > 0.05). Finally, no differences in plantar pressures by playing surface were found. In sum, the differences in the mechanical properties of the two futsal surfaces affected the performance of futsal players in the modified agility test. However, these differences were not great enough to generate different plantar pressures on players, probably due to players own adaptations.